Benchmarking an international journal. - Francis, Graham; Humphreys, Ian (Benchmarking: An International Journal., 2005)
December 2003 marked the 100th anniversary of the first heavier than air controlled, powered flight by the Wright Brothers. Since then the aviation business has changed beyond all recognition and in doing so has shrunk the globe and profoundly affected global business and the way we live.